2014
DOI: 10.1371/journal.pcbi.1003528
|View full text |Cite
|
Sign up to set email alerts
|

Identification of New IκBα Complexes by an Iterative Experimental and Mathematical Modeling Approach

Abstract: The transcription factor nuclear factor kappa-B (NFκB) is a key regulator of pro-inflammatory and pro-proliferative processes. Accordingly, uncontrolled NFκB activity may contribute to the development of severe diseases when the regulatory system is impaired. Since NFκB can be triggered by a huge variety of inflammatory, pro-and anti-apoptotic stimuli, its activation underlies a complex and tightly regulated signaling network that also includes multi-layered negative feedback mechanisms. Detailed understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…(Ambrosi et al, 2014;Kearns and Hoffmann, 2009;O'Dea et al, 2007). In particular, it was shown that free IκB is an important regulatory target for the control of Toll signals (Konrath et al, 2014). In Drosophila, Cact partitions between free and NFκB-bound complexes.…”
Section: Results and Discussion Cact Augments Responses To High Toll mentioning
confidence: 99%
“…(Ambrosi et al, 2014;Kearns and Hoffmann, 2009;O'Dea et al, 2007). In particular, it was shown that free IκB is an important regulatory target for the control of Toll signals (Konrath et al, 2014). In Drosophila, Cact partitions between free and NFκB-bound complexes.…”
Section: Results and Discussion Cact Augments Responses To High Toll mentioning
confidence: 99%
“…It appears that newly synthesized IκB rapidly re-associates with newly released NF-κB, thereby markedly reducing the amount of NF-κB translocated into the nucleus for the activation of cytokine genes. The activity of the NF-κB transcription factor is regulated by p-IκB through multiple intracellular signal transduction pathways (42).…”
Section: Discussionmentioning
confidence: 99%
“…IL-1 causes canonical activation of NF-κB, whereas UVB activates p53. In parallel, UVB-induced inhibition of PP2Ac allows for nuclear persistence of NF-κB ( Barisic et al , 2008 ; Witt et al , 2009 ; Barisic et al , 2010 ; Zhang et al , 2011 ; Konrath et al , 2014 ) and warrants prolonged activation of p65 and CREB. The fact that NF-κB activity still vanishes at later times point can be attributed to other IκB members, such as IκBɛ, that take over NF-κB inhibition in a delayed and more linear manner ( Hoffmann et al , 2002 ).…”
Section: Discussionmentioning
confidence: 99%